Pengaruh Penerapan Green Accounting dan Kinerja Lingkungan Terhadap Kinerja Perusahaan - Amanda Bellamy; Lilik Handajani; Iman Waskito (Valid: Jurnal Ilmiah, 2023)
Environmental problems are an interesting issue to study, because the company's current goal is not only to increase profits, but also to take responsibility for environmental problems that arise as a result of company operations. This study aims to examine the effect of green accounting and environmental performance on company performance. Samples obtained by 30 PROPER participating companies listed on the Indonesia Stock Exchange for 2017-2021 were tested using multiple linear regression analysis. The results of the study show that green accounting has a negative and insignificant effect on company performance. The application of green accounting through environmental disclosures made by companies voluntarily has not been able to affect the company's performance. Environmental performance has a negative and insignificant effect on company performance. The environmental performance assessment with the PROPER assessment by KLH cannot yet be the basis for determining whether a company's performance is high or low. The results of this study reject stakeholder theory and legitimacy theory, PROPER participating companies apply green accounting and environmental performance has not been able to increase stakeholder trust and community legitimacy.